Loneliness, social isolation, and all-cause mortality in the United States - Andrew C. Stokes; Wubin Xie; Dielle J. Lundberg; Dana A. Glei; Maxine A. Weinstein (Elsevier, 2021)
Social isolation and loneliness are both established risk factors for mortality, but it remains unclear how these two conditions interact with each other. We used data from 3975 adults aged 25-74 years who completed self-administered questionnaires (SAQs) for the Midlife in the United States (MIDUS) National Study Wave 2 (2004-2006). Loneliness was measured by asking participants how often they felt lonely. A shortened version of the Berkman-Syme Social Network Index that captured partnerships, friends/family, religious participation, and other forms of social connection was used to assess social isolation. Follow-up for all-cause mortality was censored at the end of 2016. We used progressively adjusted Cox proportional hazard models to examine the mortality risks of loneliness, social isolation, the components of social isolation, and combinations of loneliness and isolation. We adjusted for sociodemographic characteristics in our first models and then added health behaviors and physical and mental health conditions in subsequent models. In the minimally adjusted model, loneliness was associated with higher mortality risk (HR, 1.34; 95% CI, 1.22-1.47), but the association was not significant in the fully adjusted model. Social isolation was significantly associated with mortality in the minimally adjusted model (HR, 1.24; 95% CI, 1.15-1.34) and the fully adjusted model (HR, 1.13; 95% CI, 1.04-1.23). Having infrequent contact with family or friends was the component of isolation that had the strongest association with mortality. Contrary to prior literature, which has found either no interaction or a synergistic interaction between isolation and loneliness, we identified a significant, negative interaction between the two measures, indicating that loneliness and social isolation may partially substitute for one another as risk factors for mortality. Both are associated with a similar increased risk of mortality relative to those who express neither; we find no evidence that the combined effect is worse than experiencing either by itself.